Disentangling the Contexts of Adolescent Substance Use: An Examination of Gender Differences - Blair, Sampson Lee; Luo, Sha (International Journal of Criminology and Sociology, 2024)
Previous studies of adolescent substance use have noted how adolescent substance use is influenced by both protective and risk factors. Additionally, researchers have also noted the gradual convergence of female and male substance use, resulting in similar substance use patterns across the two. Using data from a nationally representative sample of high school seniors, this study examines the distinct effects of contextual factors upon the substance use by adolescent females and males. While both girls and boys do report similar patterns of substance use, the analyses demonstrate that peer, family, school, and work contexts affect females’ and males’ substance use in different manners. While peers readily affect drinking behaviors of each sex, peer influence yields significant associations with females’ vaping, but not males’. Among males, family contextual factors are associated with both vaping and marijuana use, while females’ vaping and marijuana use are more substantially affected by school and work contexts. The findings of this study, along with the implications thereof, are framed within the ecodevelopmental perspective.